Kajian Penanda Genetik Gen Sitokrom b DNA Mitokondria Ikan Lais dari Sungai Kampar Riau - Elvyra, Roza; Solihin, Dedy Duryadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2007)
The mitochondrial cytochrome b (cyt-b) gene as a phylogenetic marker of lais fish Kryptopterus schilbeides from Kampar River in Riau has been studied. This is a prelimininary research on the utility of cyt-b gene as a molecular marker to obtain species diversity and phylogenetic relationship among Kryptopterus fishes from Kampar River. The primers of L14841 and H15149 were used to amplify the cyt-b gene. The results showed that K. schilbeides has isoleusine at site-81 and metionine at site-114; K. schilbeides from Kampar River and K. schilbeides from GenBank form a phylogeny cluster at 45% value.